Using the Nursing Interventions Classification to identify nursing interventions in free-text nursing documentation in adult psychiatric outpatient care setting - Maria Ameel; Hanna Leino; Raija Kontio; Theo van Achterberg; Kristiina Junttila (WILEY, 2022)
Aims and objectives: To identify and describe nursing interventions in patient documentation in adult psychiatric outpatient setting and to explore the potential for using the Nursing Interventions Classification in documentation in this setting.
Background: Documentation is an important part of nurses' work, and in the psychiatric outpatient care setting, it can be time-consuming. Only very few research reports are available on nursing documentation in this care setting.
Methods: A qualitative analysis of secondary data consisting of nursing documentation for 79 patients in four outpatient units (years 2016-2017). The data consisted of 1,150 free-text entries describing a contact or an attempted contact with 79 patients, their family members or supporting networks and 17 nursing care summaries. Deductive and inductive content analysis was used. SRQR guideline was used for reporting.
Results: We identified 71 different nursing interventions, 64 of which are described in the Nursing Interventions Classification. Surveillance and Care Coordination were the most common interventions. The analysis revealed two perspectives which challenge the use of the classification: the problem of overlapping interventions and the difficulty of naming group-based interventions.
Conclusion: There is an urgent need to improve patient documentation in the adult psychiatric outpatient care setting, and standardised nursing terminologies such as the Nursing Interventions Classification could be a solution to this. However, the problems of overlapping interventions and naming group-based interventions suggest that the classification needs to be further developed before it can fully support the systematic documentation of nursing interventions in the psychiatric outpatient care setting.
Relevance to clinical practice: This study describes possibilities of using a systematic nursing language to describe the interventions nurses use in the adult psychiatric outpatient setting. It also describes problems in the current free text-based documentation.